2022
DOI: 10.3389/fbuil.2022.878197
|View full text |Cite
|
Sign up to set email alerts
|

A Nature-Based Solution for Coastal Protection: Wind Tunnel Investigations on the Influence of Sand-Trapping Fences on Sediment Accretion

Abstract: Sand-trapping fences are a frequently used nature-based solution in coastal protection for initiating and facilitating coastal dune toe growth. However, only a few researchers have evaluated the trap efficiency of sand-trapping fences based on their porosity and height. Subsequently, the design of their properties has only been based on empirical knowledge, to date. However, for restoring and maintaining coastal beach–dune systems, exact knowledge of sand-trapping fence’s optimal properties is essential. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Continued evaluation included assessing the reliability Lastly, when looking into the relationship between wind velocities and fence effectiveness, the need for further research presents itself. Recent results from field experiments conducted at coastal dunes and on sand-trapping fences underline this need for knowledge on aeolian sediment transport rates and the interaction with coastal protection measures [155]. But their study showed that empirical transport models could not be applied between the sand-trapping fence due to the absence of a logarithmic wind profile, indicating a more complex interaction between the wind flow and the fence structure that impacts sediment transport rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Continued evaluation included assessing the reliability Lastly, when looking into the relationship between wind velocities and fence effectiveness, the need for further research presents itself. Recent results from field experiments conducted at coastal dunes and on sand-trapping fences underline this need for knowledge on aeolian sediment transport rates and the interaction with coastal protection measures [155]. But their study showed that empirical transport models could not be applied between the sand-trapping fence due to the absence of a logarithmic wind profile, indicating a more complex interaction between the wind flow and the fence structure that impacts sediment transport rates.…”
Section: Discussionmentioning
confidence: 99%
“…With denser fence porosity, the deposited sediment on the windward side of the sand-trapping fence increased. The sediment accretion on the leeward side of the fence developed simultaneously but faster than the sediment accretion on the windward side of the fence [155].…”
Section: Fencesmentioning
confidence: 95%
See 2 more Smart Citations